AN ONLINE LEARNING MODEL TO FACILITATE LEARNERS’ RIGHTS TO EDUCATION - Lin, Lin (Online Learning, 2008)
This paper connects an online learning model to the rights to education that the online educational environments can provide. The model emerges from a study of ninety-two online learners and is composed of three kinds of inquiries, namely, independent inquiry, collaborative inquiry, and formative inquiry towards expert knowledge. Online learners naturally pursue and undertake these inquiries when they are equipped with communication channels and technologies. This model provides a thinking tool for integrating new media and technologies in an online learning environment in order to help students achieve their full rights to education.